Viruses as potential pathogenic agents in systemic lupus erythematosus. (May 2014) - Nelson, P; Rylance, P; Roden, D; Trela, M; Tugnet, N
Genetic and environmental factors appear to contribute to the pathogenesis of systemic lupus erythematosus (SLE). Viral infections have been reported to be associated with the disease. A number of exogenous viruses have been linked to the pathogenesis of SLE, of which Epstein-Barr virus (EBV) has the most evidence of an aetiological candidate. In addition, human endogenous retroviruses (HERV), HRES-1, ERV-3, HERV-E 4-1, HERV-K10 and HERV-K18 have also been implicated in SLE. HERVs are incorporated into human DNA, and thus can be inherited. HERVs may trigger an autoimmune reaction through molecular mimicry, since homology of amino acid sequences between HERV proteins and SLE autoantigens has been demonstrated. These viruses can also be influenced by oestrogen, DNA hypomethylation, and ultraviolet light (UVB) exposure which have been shown to enhance HERV activation or expression. Viral infection, or other environmental factors, could induce defective apoptosis, resulting in loss of immune tolerance. Further studies in SLE and other autoimmune diseases are needed to elucidate the contribution of both exogenous and endogenous viruses in the development of autoimmunity. If key peptide sequences could be identified as molecular mimics between viruses and autoantigens, then this might offer the possibility of the development of blocking peptides or antibodies as therapeutic agents in SLE and other autoimmune conditions.